2018
DOI: 10.1038/s41598-018-24562-1
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomic analysis of embryonic developmental stages in Amur sturgeon, Acipenser schrenckii

Abstract: The Amur sturgeon, Acipenser schrenckii, is an important aquaculture species in China with annual production of about 150 thousand tons in 2015. In this study, we investigated the regulatory proteins and pathways affecting embryonic development of Amur sturgeon, by analyzing of the differential proteomes among four embryonic developmental stages using isobaric tags for relative and absolute quantitation (iTRAQ), combined with the analysis of effects of microelements and antioxidants on embryonic development. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The results is interesting and may be explained by a related report, which indicated that DMSO-based vitrificant solutions were suitable for cryopreservation of Persian sturgeon (A. persicus) embryos [10]. Moreover, a recent report indicated that the dramatically high level of malondialdehyde (MDA) across the embryonic development may be the main reason leading to a low hatching rate in A. schrenckii [19]. Probably, Development in Amur Sturgeon (Acipenser schrenckii) we also speculate that low hatching rate in the MT group may be related with high expression level of MDA.…”
Section: Discussionmentioning
confidence: 92%
“…The results is interesting and may be explained by a related report, which indicated that DMSO-based vitrificant solutions were suitable for cryopreservation of Persian sturgeon (A. persicus) embryos [10]. Moreover, a recent report indicated that the dramatically high level of malondialdehyde (MDA) across the embryonic development may be the main reason leading to a low hatching rate in A. schrenckii [19]. Probably, Development in Amur Sturgeon (Acipenser schrenckii) we also speculate that low hatching rate in the MT group may be related with high expression level of MDA.…”
Section: Discussionmentioning
confidence: 92%
“…Proteins are responsible for most of the enzymatic reactions and the structural organization of cells and organisms. , It is now clear that different physiological states or stresses can affect the expression of specific proteins. Although it is well-known that the genome is largely stable across the life of an organism, the deployment of the proteome remains elusive. Although many studies have linked molecular markers with particular phenotypes, notably through the identification of quantitative trait locus (QTL), , few have investigated changes in the proteome between, for example, different developmental states, and the relation between phenotype and proteome is still not well-defined. , To monitor changes in the proteome between two very different developmental states of an organism, quantitative mass-spectrometry is a particularly suitable method . Recent MS approaches based on Data Independent Acquisition (DIA) methods, such as SWATH-MS, combine deep proteome coverage with ions selectivity similar to targeted proteomics, resulting in precise quantification of a large number of proteins. , With its small size and short life cycle, features that allow large cohorts of individuals to be rapidly collected, Drosophila melanogaster is a model organism particularly well-suited to study development and aging .…”
Section: Introductionmentioning
confidence: 99%
“…However, the understanding of the role of miRNAs associated with grass carp disease is still limited. Isobaric tags for relative and absolute quantification (iTRAQ) are widely used in proteomics due to their numerous advantages [ 33 , 34 ]. These advantages include high detection efficiency, simplified mass spectrometer complexity, improved ion abundance, the enhanced coverage and reliability of protein identification, a simple and efficient labelling process, and a wide range of applications [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%